2010
DOI: 10.1111/j.1365-2753.2010.01586.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of tailored communication for person‐centred outcomes

Abstract: There is empirical evidence for the value of tailored communication for person-centred outcomes. Communicating in a purposeful way while at the same time respecting patients' values and feelings should therefore become the standard in health care practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 16 publications
3
22
0
1
Order By: Relevance
“…Also in line with other studies, we found that pharmacy staff members were friendly and respectful to patients, had sufficient eye contact, and left room for patients’ comments [19–21]. However, they did not encourage active patient participation, as they did not ask for patients’ needs and preferences.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Also in line with other studies, we found that pharmacy staff members were friendly and respectful to patients, had sufficient eye contact, and left room for patients’ comments [19–21]. However, they did not encourage active patient participation, as they did not ask for patients’ needs and preferences.…”
Section: Discussionsupporting
confidence: 85%
“…Effective and efficient patient‐centred encounter depends on both the pharmacy staff and the patient having an active role. The pharmacy staff need to explore patient's preferences and to provide the patient with medical information that would help the patient make the right decisions [16–21]. The patient should be honest about their needs and concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Patients should express perceived side effects and their beliefs and concerns. This results in an effective and efficient patient-centered encounter in which a patient perceives support and care [13][14][15].…”
Section: Introductionmentioning
confidence: 96%
“…Research shows that tailored communication positively influences clinical and health outcomes known to be crucial for recovery and quality of life, including information recall, adherence to treatment and advice, reassurance and fulfilment of individual needs (van Dulmen, ; Meterko, Wright, Lin, Lowy, & Cleary, ). Effective communication is defined as a pattern of exchanging information and ideas with others that is sufficient for meeting one's needs and life goals (Herdman, ).…”
Section: Introductionmentioning
confidence: 99%